Comparative Aspects of Labor Movements - White, Rodney (Relations industrielles / Industrial Relations, 1959)
SummaryAlthough the volume of research in the labor field is increasing all the time, there is a pressing need for more studies using a comparative approach. In this article the author outlines what he considers to be a useful framework for making comparative studies of labor movements and illustrates it by applying it to an analysis of the American labor movement with some suggestions as to its application in other countries.